Women's Hebrew Poetry on American Shores : Poems by Anne Kleiman and Annabelle Farmelant - Kleiman, Anne, 1909-2011; Farmilanṭ, Ḥanah (Book collections on Project MUSE., 2016)
Presents the work of two American-born women, Anne Kleiman and Annabelle Farmelant, who wrote and published a substantial body of Hebrew poetry between the 1930s and 1960s. Editor Shachar Pinsker recovers the singular voices of these women, introducing their captivating and wide-ranging poetry and placing it in its historical, literary, and cultural contexts.